(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2020)
Introduction. The article is devoted to the lack of research into the nature, structure and socio-economic importance of the use of energy from renewable sources. A huge array of fundamental and applied research of scientists in the context of ensuring the development of energy resources from renewable sources of origin has been elaborated; the excursion of the use of renewable energy sources by the developed countries of the world is made in the conditions of limited fossil fuel reserves, limitation according to the Kyoto Protocol of greenhouse gas emissions and in the context of compliance with energy security standards. The specific features and types of energy resources of renewable origin are structured according to the level of their use in the economic functions of regional systems. The energy potential of Ukrainian regions in relation to the implementation of modern RES methods and methods has been determined. The quantity and objectivity of the centers of introduction of energy supply of RES in the regions of Ukraine have been clarified. The research conducted earlier is summarized and the directions of scientific, industrial, technological and infrastructural overcoming of obstacles for the introduction of widespread use of RES in the socio-economic environment of the regions are proposed. The purpose of the article. Тhe purpose of this work is to review the nature and efficiency of renewable energy sources, to find out their energy potential in the regional context and to outline ways to improve the practice of using renewable energy sources in the country’s economic circulation. The outlined goal led to a further solution of a number of problems: - specification of the nature, nature and methods of application of RES; - practical experience in achieving a proper supply of RES in EU countries; - social and economic effects from the introduction of regional energy systems with an increased share of RES, unlike traditional energy; - probable ways of diversification of energy resources from renewable energy sources in Ukraine; - monitoring of certain energy potential of regions of Ukraine.